Tingkat Penerapan Jurnalisme Lingkungan dalam Pemberitaan Isu Eksploitasi Kawasan Bentang Alam Karst (KBAK) Gunung Sewu di Media Daring Suara.com dan Harian Jogja (Analisis Isi Kuantitatif Pemberitaan Isu Eksploitasi Kawasan Bentang Alam Karst (KBAK) Gunu - Zahra, Yasmina Shofa Az; Agustin, Herlina; Basith, Achmad Abdul (Jurnal Ilmiah Global Education, 2024)
The exploitation of the protected land of the Karst Landscape Conservation Area (KBAK) of Gunung Sewu for the construction of Raffi Ahmad's Bekizart Beach Club will have implications for the disruption of environmental sustainability and the well-being of the local community. Mass media coverage of conflicts in environmental management is closely related to the application of environmental journalism (Sudibyo, 2014). This research aims to determine the level of application of environmental journalism in online medias Suara.com and Harian Jogja in reporting on the construction of Bekizart Beach Club during the period of December 2023 to January 2024 based on four principles of environmental journalism by Sudibyo (2014): sustainability, biosentrics, environmental justice, and professionalism. The method used is quantitative content analysis by Kripendorff (2004). The results show that the level of application of the pro-sustainability principle in Suara.com is 70.84%, categorized as high, while in Harian Jogja, it is 26.67%, categorized as low. The application of the biosentrics principle in Suara.com is 56.25%, categorized as medium, while in Harian Jogja, it is 30%, categorized as low. The application of the environmental justice principle in Suara.com is 34.38%, categorized as low, while in Harian Jogja, it is 10%, categorized as very low. The application of the professionalism principle in Suara.com is 56.25%, categorized as medium, while in Harian Jogja, it is 40%, categorized as medium. Increasing supervision and journalists' understanding of the application of environmental journalism principles need to be done through training and the establishment of regulations regarding reporting on environmental issues in each mass media.